2019
DOI: 10.1097/iop.0000000000001209
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-analysis of Methods for Reducing Local Anesthetic Injection Pain Among Patients Undergoing Periocular Surgery

Abstract: Purpose: Various factors help minimize pain during the injection of local anesthetic. The majority of current evidence involves nonspecific injection sites. The objective of this review was to provide a comprehensive summary of all existing evidence for methods used to reduce injection pain specifically in the context of periocular procedures. Methods: A literature search of the MEDLINE, EMBASE, and Scopus databases was conducted to identify all relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Recently, a systematic review including 23 randomised controlled trials investigated local anaesthesia in periocular procedures. 22 Only one of these studies examined the needle type as an equipment factor. 21 Forty four patients (mean age=31) undergoing blepharoplasty used a blunt 27-gauge needle, which has the same thickness as a conventional sharp needle, to compare pain, bruising, and hematoma formation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, a systematic review including 23 randomised controlled trials investigated local anaesthesia in periocular procedures. 22 Only one of these studies examined the needle type as an equipment factor. 21 Forty four patients (mean age=31) undergoing blepharoplasty used a blunt 27-gauge needle, which has the same thickness as a conventional sharp needle, to compare pain, bruising, and hematoma formation.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] Furthermore, various studies have reported factors that help minimise pain during local anaesthesia, which include the choice of the anaesthetic agent, dilution, buffering, and skin cooling. 22 Anaesthetic injections can also lead to tissue distortion and bleeding, which further distort the anatomical structures, making it more di cult to perform surgery accurately; thus, care should be taken to limit these. 3 4 21 Various studies have been conducted to nd factors that reduce the pain of anaesthetic injections.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…PS has been explored as an alternative local anaesthetic option for a variety of indications. These include pain associated with: venipuncture [ 13 ], insertion of intravenous catheters [ 14 – 17 ], subcutaneous drug administration [ 18 ], intravenous drug administration [ 10 ], intra-articular injections [ 19 ], cervical dilatation for suction and curettage [ 20 ], periocular surgery [ 21 24 ] and periocular botulinum toxin A injections [ 25 28 ].…”
Section: Methodsmentioning
confidence: 99%